Eksplorasi Jenis Jamur Makroskopis di Kawasan Bukit Gatan Kabupaten Musi Rawas Provinsi Sumatera Selatan - Larseh Putri Anggraini; Harmoko; Nopa Nopiyanti (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This study aims to determine the types of macroscopic fungi in Bukit Gatan, Musi Rawas Regency, and Abiotic Factors found in Bukit Gatan, Musi Rawas Regency. This research is descriptive, direct observation at the location of Bukit Gatan, Musi Rawas Regency by using the method of exploring with one hiking trail. Data were analyzed descriptively qualitatively. The type of fungus in the hiking trail are 2 divisions namely Basidiomycota and Ascomycota. The Basidiomycota Division found 7 orders, 12 families, 15 genera and 19 species, namely Pleurotus ostreatus, Pleurotus pulmonarius, Leptiota brunneoincarnata, Marasmius candidus, Schizophyllum commune, Entoloma procerum, Ganoderma l, Ganoderma lucidum, Leptiota brunneoincarnata, Marasmius candidus, Schizophyllum commune, Entoloma procerum, Ganoderma l, Ganoderma lucidum, Leptiota brunneoincarnata, Marasmius candidus, Schizophyllum commune, Entoloma procerum, Ganoderma l, Ganoderma lucidum, Earliverus gustulus sacraicusus , Clitocybe salmonilamella, Phallus indusiatus, Coltricia cinamomea, and Coltricia perennis. Ascomycota Division produces 2 orders, 2 families, 3 genera and 3 species namely Cookeina sulcipes, Daldinia conentria, and Xylaria longipes. The abiotic factors are the temperature of 29-31 ° C, pH between 6-7, humidity of 30-70%, light intensity of 200 lux and height of 72-241 masl.